PELATIHAN KEWIRAUSAHAAN DAN PERHITUNGAN AKUNTANSI BIAYA UNTUK PENINGKATAN EKONOMI DI DESA MUARA - Nugraheni, Novita; Paramitha, Diky; Solihat , Iis; Widiastuti, Yeni; Firman, Antares; Abdurrohman Thohir Wijaya, Raden (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Micro, Small, and Medium Enterprises (MSMEs) constitute a burgeoning economic sector in Indonesia. SME empowerment policies primarily aim to promote initiatives that mitigate poverty and inequality, generate employment opportunities, enhance exports, and rejuvenate agricultural and rural regions, which were national development priorities in 2006. This community service imparts knowledge of entrepreneurship and emphasizes the significance of calculating the cost of goods sold (COGS) to MSME entrepreneurs in Muara Village, Tangerang Regency. This aims to enable them to ascertain the business plan to implement and maximize profits in a competitive landscape with analogous products while preventing excessive budgeting in merchandise production. The Community Service (PkM) is situated in Muara Village. Muara Village is situated in the northern part of Teluk Naga District. The aims of this community service program are: Imparting information and skills to MSMEs in Muara Village, Teluk Naga District, Tangerang Regency, specifically with training on the calculation of Cost of Goods Sold. Participants are provided with instructions on capturing images intended for the marketing of their items. Participants receive instruction on computing the Cost of Goods Sold (COGS).